Who Becomes an Entrepreneur? A 30-Years-Review of Individual-Level Research and an Agenda for Future Research - Simon Heinrichs; Sascha Walter (ZBW - Leibniz-Informationszentrum Wirtschaft, 2013)
This article reviews the theoretical background and cumulates findings of 126 published studies (1980 - 2009) on individual determinants of entrepreneurial status. We categorize determinants into one of six paradigms (trait, cognitive, affective, intentions, learning, and economic) and review findings for 46 repeatedly studied variables. We then examine trends in the field and propose an agenda for future research. Our article complements prior reviews and meta-analyses by picturing the breadth of the field and adding important points to the research agenda.
Keywords: M13; 650; entrepreneurial status; Unternehmensgründung